2022
DOI: 10.1038/s41598-022-11985-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the coexistence of gaming and viewing activities in Twitch users and their relationship with pathological gaming: a multilayer perceptron approach

Abstract: The enormous expansion of the video game sector, driven by the emergence of live video game streaming platforms and the professionalisation of this hobby through e-sports, has spurred interest in research on the relationships with potential adverse effects derived from cumulative use. This study explores the co-occurrence of the consumption and viewing of video games, based on an analysis of the motivations for using these services, the perceived positive uses, and the gamer profile. To that end, a multilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 113 publications
1
5
0
Order By: Relevance
“…Moreover, they emphasize the importance of considering various forms of gaming involvement when assessing GD risk. Our findings are in line with previous research focused on individual components of IGI: Cabreza-Ramirez et al ( 14 ) showed that a feeling of belonging to the Twitch community (a service mainly focused on video game streaming) plays an important role in the model of pathological game use; Ortiz de Gortari et al showed that intrusive thoughts regarding gaming are correlated with GD ( 16 ). Interestingly, Yildiz Durak et al ( 17 ) showed that time spent watching gaming videos on Twitch is correlated with GD, whereas time spent watching gaming streams on unspecified platforms or gaming itself is not linked to GD.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, they emphasize the importance of considering various forms of gaming involvement when assessing GD risk. Our findings are in line with previous research focused on individual components of IGI: Cabreza-Ramirez et al ( 14 ) showed that a feeling of belonging to the Twitch community (a service mainly focused on video game streaming) plays an important role in the model of pathological game use; Ortiz de Gortari et al showed that intrusive thoughts regarding gaming are correlated with GD ( 16 ). Interestingly, Yildiz Durak et al ( 17 ) showed that time spent watching gaming videos on Twitch is correlated with GD, whereas time spent watching gaming streams on unspecified platforms or gaming itself is not linked to GD.…”
Section: Discussionsupporting
confidence: 92%
“…In consequence, they may spend a great percentage of their time on such activities, ultimately leading them to GD. As shown by Cabeza-Ramirez and colleagues ( 14 ), DGI is associated with IGI (in this case: time spent watching game-related streams), and, as these authors suggest, depending on the prioritization of each activity, the effects on GD may vary. Thus, both DGI and IGI should be explored.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, psychological distress is sometimes associated with addictive use of video games but is unrelated to frequent use (Király, Tóth, et al, 2017). Similarly, Twitch viewing time appears to be unrelated to negative outcomes (e.g., overspending, escapism; Cabeza-Ramírez, Rey-Carmona, et al, 2022). Study 2 seeks further evidence for this distinction.…”
Section: The Popularity Of Twitch and Current Research Perspectivesmentioning
confidence: 98%